Теоретико-правові засади проведення судово-психіатричної експертизи у кримінальному провадженні - Макарова, О. П.; Makarova, O. P. (Право і безпека. – 2023. – № 3 (90). – С. 190-199, 2023)
Визначено теоретико-правові аспекти призначення та проведення судово-психіатричної експертизи на підставі аналізу положень нормативно-правових актів у цій сфері. Висвітлено питання щодо професійної складової підготовки експертів, які проводять судово-психіатричну експертизу, з’ясовано, що зазвичай вони мають свій індивідуальний стиль професійної діяльності, постійно підвищують і вдосконалюють рівень власної компетентності. З’ясовано, що предметом дослідження психіатра є психічні захворювання та розлади, захворювання головного мозку, які проявляються розладами психічної діяльності особистості. Розглянуто питання етичних стандартів у діяльності експерта при проведенні судово-психіатричної експертизи.

The category of forensic examinations includes examinations conducted in civil or criminal proceedings by court order. Forensic examinations are carried out in specialised forensic institutions or outside these institutions in accordance with the procedure established by law. A significant number of forensic examinations are conducted in forensic departments of state psychiatric institutions. According to Ukrainian legislation, state forensic institutions are those institutions that are specifically designated to conduct forensic examinations and are subordinate to the Healthcare Department. A forensic psychiatric or comprehensive forensic psychological and psychiatric examination must be conducted by experts in accordance with the procedure set out in the Civil Procedure and Criminal Procedure Codes of Ukraine. Depending on the nature of the expert research, forensic psychiatric examination departments are divided into outpatient and inpatient. The knowledge that a psychiatric expert must have is specific, taking into account knowledge of the patterns and characteristics of mental activity of the individual. This specialised knowledge is acquired during special professional psychological and psychiatric training, and is subsequently implemented in the practice of forensic psychiatric examination, and therefore has legal significance. The knowledge used in the pre-trial investigation of criminal offences and in court proceedings is used to establish the mental state of the person who committed the criminal offence. The theoretical and legal aspects of the appointment and conduct of forensic psychiatric examination have been determined on the basis of the analysis of the provisions of legal acts in this area. The issues related to the professional component of training of experts conducting forensic psychiatric examination have been highlighted, and it has been found that, as a rule, they have their own individual style of professional activity and constantly improve their level of competence. It has been found out that the subject of psychiatrist's research is mental diseases and disorders, brain diseases manifested by disorders of mental activity of a person. The issues of ethical standards in the activities of an expert in conducting a forensic psychiatric examination have been considered.

Определены теоретико-правовые аспекты назначения и проведения судебно-психиатрической экспертизы из анализа положений нормативно-правовых актов в этой сфере. Освещены вопросы профессиональной составляющей подготовки экспертов, которые проводят судебно-психиатрическую экспертизу, выяснено, что обычно они имеют свой индивидуальный стиль профессиональной деятельности, постоянно повышают и совершенствуют уровень собственной компетентности. Выяснено, что предметом исследования психиатра являются психические заболевания и расстройства, заболевания головного мозга, проявляющиеся расстройствами психической деятельности личности. Рассмотрены вопросы этических стандартов в деятельности эксперта при проведении судебно-психиатрической экспертизы.
Theoretical and legal principles of forensic psychiatric examination in criminal proceedings
Keywords: кримінальне провадження; судово-психіатрична експертиза; експерт; професійна компетентність; психіатр; спеціаліст; criminal proceedings; forensic psychiatric examination; expert; professional competence; psychiatrist; specialist; уголовное производство; судебно-психиатрическая экспертиза; эксперт; профессиональная компетентность; психиатр; специалист